Social and Economic Barriers to Subsistence Harvesting in a Northern Alberta Aboriginal Community - Nelson, Mark; Natcher, David C.; Hickey, Clifford G. (Anthropologica, 2022)
A community survey conducted in the Little Red River Cree Nation of northern Alberta identified several socio-economic barriers that impede peoples’ ability to spend time in the bush and to engage in subsistence harvesting. This paper presents the results of the community survey, along with a discussion of the impacts of reduced harvesting and several options for mitigating harvesting barriers. The practice of subsistence harvesting is understood here as being essential for the enactment and maintenance of certain local social systems and cultural values.